The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1302/0301-620x.97b1.34492
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of the fracture level in the treatment of Gartland type III supracondylar humeral fracture in children

Abstract: A small proportion of children with Gartland type III supracondylar humeral fracture (SCHF) experience troubling limited or delayed recovery after operative treatment. We hypothesised that the fracture level relative to the isthmus of the humerus would affect the outcome. We retrospectively reviewed 230 children who underwent closed reduction and percutaneous pinning (CRPP) for their Gartland type III SCHFs between March 2003 and December 2012. There were 144 boys and 86 girls, with the mean age of six years (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…Further prognostic factors including the level of the fracture and the patient age at time of surgery have been proved important. Kang et al [47] revealed that fractures below the humeral isthmus are associated with poor outcome after surgical treatment. Commonly used classification systems as the classifications according to Gartland [41], Baumann [48], Lagrange and Rigault [49] or the AO Pediatric Comprehensive Classification of Long Bone Fractures [50] do not lay stress on the fracture level and therefore do not detect this prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…Further prognostic factors including the level of the fracture and the patient age at time of surgery have been proved important. Kang et al [47] revealed that fractures below the humeral isthmus are associated with poor outcome after surgical treatment. Commonly used classification systems as the classifications according to Gartland [41], Baumann [48], Lagrange and Rigault [49] or the AO Pediatric Comprehensive Classification of Long Bone Fractures [50] do not lay stress on the fracture level and therefore do not detect this prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…(15). Fracture is more common in boys (Table 1); this is explained by the fact that boys are more restless than girls (16). Despite the high incidence, we still do not have a generally accepted treatment for this fracture.…”
Section: Resultsmentioning
confidence: 99%
“…In supracondylar fractures, periosteum is detached from distal fragment. Small amount of distal fragment with torn periosteum in low-level supracondylar humerus fractures could make closed reduction challenging with risk of dynamic unstable fixation which is stated by Kang et al [11] The small distal fracture fragment precludes insertion of the wires from the appropriate points, and the inserted wires have reduced holding power, which makes it difficult to achieve closed reduction. These factors all demonstrate that fracture configuration is an important guide in planning surgical treatment and assessing clinical outcomes in supracondylar humerus fractures in children.…”
Section: Discussionmentioning
confidence: 99%
“…[3,4] Various studies have suggested associations between conversion to open reduction and factors such as time to operation, patient weight, surgeon experience, and excessive edema around the fracture; [5] however, no consensus has been reached regarding which patients are more likely to require conversion to open reduction. [6][7][8][9][10][11] Gartland type III fractures occur in the distal humerus and may be located above the isthmus (high level) (Fig. 1) or at/ below the isthmus (low level) (Fig.…”
Section: Introductionmentioning
confidence: 99%